Commodification of elections: the future of elections in Zimbabwe - Obert Hodzi (Modern Africa, 2014)
The economic voting theory and the responsibility hypothesis posit that voters hold the government accountable for economic performance and will vote for the incumbent if the economy is good. The core assumption is that there is an incumbent and an opposition contesting in an election. But, this is not always the case. In elections following a transitional power sharing government, the schism between the incumbent and the opposition is generally blurred. Political parties that usually contest in the elections would have been part of the transitional power-sharing government. In such cases, voters are not able to apportion responsibility, and political parties compete to claim credit and assign blame. This increases the propensity for election commodification. Applying this proposition to Zimbabwe’s 2013 elections, this paper contends that commodification of elections increases in polls following a transitional power sharing government when political parties contesting in the elections were part of the transitional power sharing government, making it difficult for voters to determine responsibility for policy, and leading to intense competition among political parties to claim credit and apportion blame for the performance of the transitional power-sharing government.